2019
DOI: 10.1007/s00283-019-09923-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer Geometry: Rep-Tiles with a Hole

Abstract: A cube is an 8-rep-tile: it is the union of eight smaller copies of itself. Is there a set with a hole which has this property? The computer found an interesting and complicated solution, which then could be simplified. We discuss some problems of computer-assisted research in geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In [45] an example with m = 24 was given and in [46] a more sophisticated and interesting example with very large m is discussed. An interesting example of a new 8−rep tile with a hole was found very recently by Bandt and Mekhontsev in [33] (see Figure 13). A tile T is called a self-affine lattice tile if there is an affine expanding mapping g and a lattice L such that g preserves L and maps T to a union of tiles T + k i with k i ∈ L. With respect to the standard basis vectors e i , the map g has a matrix representation g(x) = Mx where M is an integer matrix.…”
Section: Fractal Rep Tiles In Rmentioning
confidence: 74%
See 1 more Smart Citation
“…In [45] an example with m = 24 was given and in [46] a more sophisticated and interesting example with very large m is discussed. An interesting example of a new 8−rep tile with a hole was found very recently by Bandt and Mekhontsev in [33] (see Figure 13). A tile T is called a self-affine lattice tile if there is an affine expanding mapping g and a lattice L such that g preserves L and maps T to a union of tiles T + k i with k i ∈ L. With respect to the standard basis vectors e i , the map g has a matrix representation g(x) = Mx where M is an integer matrix.…”
Section: Fractal Rep Tiles In Rmentioning
confidence: 74%
“…We also refer to the recent works on fractal tilings by Bandt and Mekhontsev [32][33][34][35] for a comprehensive summary and current state of the art in the subject. The use of the inverses of integer matrices in the study of tilings is well-established, and can be found in particular in many of the references cited above.…”
Section: Fractals In Tessellationmentioning
confidence: 99%
“…With two or three pieces, we have few degrees of freedom, and only a small number of IFS with OSC, most of which are well known [35,36]. With eight or nine pieces, we already have a huge choice of parameters s k and v k which we cannot control even with a computer (see [6] for discussion of a similar case). A maximal number of five pieces is better to handle.…”
Section: Basic Assumptions and A Simple Examplementioning
confidence: 99%
“…Computer studies with our package IFStile [3] revealed a huge number of new examples of this sort, with quite unexpected symmetries and properties. Starting with [4], see also [5,6], we have tried to present new classes of fractal sets in a systematic way. Here we focus on examples from quadratic number fields.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the the self-affine partitions of polyhedra have also been studied under less restrictive conditions, when not only parallel translations but also rotations are allowed [1,3,16,18].…”
Section: Introductionmentioning
confidence: 99%